2017
DOI: 10.1002/gdj3.44
|View full text |Cite
|
Sign up to set email alerts
|

The automatic weather stations NOANN network of the National Observatory of Athens: operation and database

Abstract: During the last 10 years, the Institute for Environmental Research and Sustainable Development of the National Observatory of Athens has developed and operates a network of automated weather stations across Greece. The motivation behind the network development is the monitoring of weather conditions in Greece with the aim to support not only the research needs (weather monitoring and analysis, weather forecast skill evaluation) but also the needs of various communities of the production sector (agriculture, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
105
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 194 publications
(134 citation statements)
references
References 23 publications
0
105
0
Order By: Relevance
“…MODIS calibrated radiances product (MOD/MYD021KM) and precipitable water product (MOD/MYD05-L2) were accessed from the National Aeronautics and Space Administration's (NASA's) Level-1 and Atmosphere Archive and Distribution System (LAADS) Distributed Active Archive Center (DAAC). Above rooftop level meteorological data-T α , barometric pressure (P), wind speed (W), relative humidity (RH), and downward solar radiation (K↓)-were provided from the network of urban AWSs of the National Observatory of Athens via its online interface ( [69]; http://stratus.meteo.noa.gr/front; Figure 1). These data were subsequently interpolated in the study area using regression kriging with elevation as an auxiliary variable [70] (K↓ was considered constant for the whole study area).…”
Section: Bowen Ratiomentioning
confidence: 99%
“…MODIS calibrated radiances product (MOD/MYD021KM) and precipitable water product (MOD/MYD05-L2) were accessed from the National Aeronautics and Space Administration's (NASA's) Level-1 and Atmosphere Archive and Distribution System (LAADS) Distributed Active Archive Center (DAAC). Above rooftop level meteorological data-T α , barometric pressure (P), wind speed (W), relative humidity (RH), and downward solar radiation (K↓)-were provided from the network of urban AWSs of the National Observatory of Athens via its online interface ( [69]; http://stratus.meteo.noa.gr/front; Figure 1). These data were subsequently interpolated in the study area using regression kriging with elevation as an auxiliary variable [70] (K↓ was considered constant for the whole study area).…”
Section: Bowen Ratiomentioning
confidence: 99%
“…The first goal of this study is to evaluate the model skill in forecasting the observed convection for the selected 10 cases by analyzing accumulated precipitation fields (as no radar data are yet available over Greece). The 24-hr simulated accumulated precipitation (APCP) for each case study are verified against observations derived from a network of 110-140 rain gauges (Figure 2), which is operated by the National Observatory of Athens (NOA; Lagouvardos et al, 2017). The six model grid points surrounding each rain gauge were considered for the computation of standard qualitative statistical measures including the probability of detection (POD) and the false alarm ratio (FAR; i.e., contingency tables).…”
Section: Precipitation Observationsmentioning
confidence: 99%
“…[21]). Meteorological datasets are complemented by measurements from the dense meteorological network operated in the greater area by the National Observatory of Athens (NOA), as well as weather forecasts for the area, also provided by NOA [19]. Extended fieldwork has been done to collect field data for the preparation of the base data like the updated landcover dataset [22].…”
Section: Project Area and Datasetsmentioning
confidence: 99%
“…From 51 prefectures of Greece, Attica was among the more often influenced areas, mostly from flash floods. Regarding the seasonality of flash floods, autumn in Greece is actually the season with the higher frequency of rainfall and the highest accumulated rainfall, particularly in the mainland [16][17][18][19]. As well, economic damages resulting from wildfires (i.e., the reduced ability of a burnt forest to offer recreation opportunities) are also significant, especially in Mediterranean regions, where their frequency is considerably high.…”
Section: Introductionmentioning
confidence: 99%